Germany : 2018 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2018)
The Germany economy has performed very well in recent years, supported by prudent economic management and past structural reforms. Growth is robust, employment is rising, and the unemployment rate has fallen to levels not seen in decades. Inflation remains low but wage growth is picking up, reflecting the strength of the labor market. Looking beyond these positive cyclical developments, unfavorable demographics will soon weigh on potential growth and put pressure on public finances. Having already accumulated sizable buffers through savings, Germany should now prioritize domestic investment in physical and human capital to prepare for the future. The new government's coalition agreement contains several welcome measures in this direction, but more forceful actions to boost labor supply and increase labor productivity would help stimulate domestic investment and reduce Germany's large current account surplus.